Antibodies to leukotoxin A from the periodontal pathogen Aggregatibacter actinomycetemcomitans in patients at an increased risk of rheumatoid arthritis - Martinsson, Klara; Di Matteo, Andrea; Öhman, Carina; Johansson, Anders; Svärd, Anna; Mankia, Kulveer; Emery, Paul; Kastbom, Alf (Frontiers in Medicine, 2023)
Objectives Periodontitis and underlying bacteria have been linked to the development of rheumatoid arthritis (RA). One suggested pathogen is Aggregatibacter actinomycetemcomitans (A.a.), which expresses leukotoxin A (LtxA) that can citrullinate human proteins, providing a possible trigger for the production of anti-citrullinated protein antibodies (ACPA). In this study, we seek to determine the presence of antibodies toward LtxA in patients at risk of developing RA. Methods Two prospective observational patient cohorts (one Swedish and one British) with symptomatic at-risk patients were studied. Anti-LtxA antibodies were analyzed by a cell-based neutralization assay in baseline serum and compared to 100 Swedish blood donors that served as controls. Results Serum anti-LtxA levels or positivity did not differ between patients and blood donors. In the British cohort, anti-LtxA was more prevalent among ACPA-positive arthralgia patients compared with ACPA-negative arthralgia cases (24% vs. 13%, p < 0.0001). In the Swedish at-risk cohort, anti-LtxA positive patients were at increased risk of progression to arthritis (hazard ratio (HR) 2.10, 95% CI 1.04–4.20), but this was not confirmed in the UK at-risk cohort (HR 0.99, CI 0.60–1.65). Conclusion Serum anti-LtxA is not elevated before RA diagnosis, and associations with disease progression and ACPA levels differ between populations. Other features of the oral microbiome should be explored in upcoming periodontitis-related RA research.